(3ehdO GdfHj Udi Gddg Ydjg hSdes - (3GdSgej, GdCSdej, GdhGbOj, CHh YHO Gddg, eMeO Hf YeQ Hf hGbO, J (B207 (3g`s
(3ChdgG (B:s
(3GdMeO ddg GdPj LYd adc GdbOQI Ydi OhQ GdMceI aj CbWGH bWH GdeLQI eSJOjQG hLYd beQ GdYRI Ydi UaGA UOa bYQ GdHMQ aj eOGQL GdchGcH eSJfjQG (B...s
(3BNQgG (B:s
... (3dMbfj ZWT TOjO aJfGhdJgG hTQHJgG aCVGA Ydj efgG fhQ YXje Ke fXQJ hGfG HWGFQ CHjV bO ONd Ydi MLQJj Ke eQ HLfGMg Ydi aDGOj (B..s
(3JHUQI GdYfhGf (B:s
(3jfaj cKjQ ef GdHGMKjf fSHJg Edi GdhGbOjs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ddRQcdj (B6/311s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
Keywords: (3GdJGQjNs